Seasonal training and performance of competitive swimmers - Stewart, A. M.; Hopkins, W. G. (Journal of Sports Sciences, 2000)
To determine the relationship between prescribed training and seasonal-best swimming performance, we surveyed 24 swim coaches and 185 of their age-group and open-class swimmers specializing in sprint (50 and 100 m) and middle-distance (200 and 400 m) events in a summer and winter season. We expressed effects on training as either multiples of swimmers' standard deviations (effect size, ES) or as correlations (r). Coaches prescribed higher mileage and longer repetitions of lower intensity to middle-distance swimmers than to sprinters (ES = 0.4-1.5); as competitions approached, repetition intensity and duration of rest intervals increased (ES = 0.5-0.9), whereas session and repetition distances decreased (ES = 0.4-1.3). The 95% likely ranges of the true values for these effects were about ± 0.3. Weekly mileage swum at an easy or moderate pace remained at almost 60% of the total throughout both seasons. Interval training reduced gradually from 40% of total distance in the build-up to 30% at the end of tapering. Older swimmers had shorter rests and swam more miles (r = 0.5-0.8). After partialling out the effects of age on performance (r = 0.7-0.8), better performance was significantly associated only with greater weekly mileage (r = 0.5-0.8) and shorter duration of rest intervals (r = 0.6-0.7) in middle-distance swimmers. Weconclude that periodization of training and differences in training between sprint and middle-distance events were broadly in accord with principles of specificity. Strong effects of specificity on performance were not apparent, but weak effects might have been detected with a larger sample.